2015
DOI: 10.1371/journal.pone.0131455
|View full text |Cite
|
Sign up to set email alerts
|

De novo Transcriptome Assembly of Common Wild Rice (Oryza rufipogon Griff.) and Discovery of Drought-Response Genes in Root Tissue Based on Transcriptomic Data

Abstract: BackgroundThe perennial O. rufipogon (common wild rice), which is considered to be the ancestor of Asian cultivated rice species, contains many useful genetic resources, including drought resistance genes. However, few studies have identified the drought resistance and tissue-specific genes in common wild rice.ResultsIn this study, transcriptome sequencing libraries were constructed, including drought-treated roots (DR) and control leaves (CL) and roots (CR). Using Illumina sequencing technology, we generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…; N50 = 1147 bp, average length = 715 bp) [65], and sugarcane ( Saccharum officinarum ; N50 = 1177 bp) [66]. Additionally, the GC content of the assembled unitranscripts (49%) was slightly higher compared to those obtained previously in A. donax (45.60% [10] and 47.70%; [11]), but it was similar to that observed in P. australis using Illumina sequencing (49.9%) [64].…”
Section: Discussionmentioning
confidence: 99%
“…; N50 = 1147 bp, average length = 715 bp) [65], and sugarcane ( Saccharum officinarum ; N50 = 1177 bp) [66]. Additionally, the GC content of the assembled unitranscripts (49%) was slightly higher compared to those obtained previously in A. donax (45.60% [10] and 47.70%; [11]), but it was similar to that observed in P. australis using Illumina sequencing (49.9%) [64].…”
Section: Discussionmentioning
confidence: 99%
“…However, the genes specifically expressed in green tissues in common wild rice have not been reported. Previously, we sequenced the transcriptome of common wild rice and identified root-specific and drought-related genes [ 30 ]. In this study, we used this dataset to screen for genes with green tissue-specific expression and cloned the promoter sequence of one of these genes, OrGSE ( O. rufipogon GREEN SPECIAL EXPRESS).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al demonstrated that CWR could be used to modify the stomatal conductance and membrane stability, which are related to drought resistance in cultivars rice [6]. Based on high-throughput sequencing, there were 901 contig responses to drought stress [7]. Therefore, there are abundant drought resistant-gene resources in CWR, providing excellent resources that can contribute to increasing the rice resistance, productivity, and quality [8].…”
Section: Introductionmentioning
confidence: 99%